Implementation of Mix Media Collage Through The Project-Based Learning Approach to Improve Independence and Learning Creativity of Grade XI Students in The Material of Personal Ekspression Works - Novi, Ayunda; Banowati, Eliya; Rambu, Najwa; Setia, Wisnu (IJESS International Journal of Education and Social Science, 2025)
This research aims to analyze the effectiveness of applying mixed media collage techniques in Project-Based Learning (PjBL) based visual arts instruction on increasing the independence and learning creativity of Grade XI students in the Personal Expression Artwork material. The background of this research is the low exploration of ideas and active participation of students in art instruction which is still dominated by conventional approaches. This research uses a qualitative approach with a case study design, involving one cohort of Grade XI students at SMAN 1 Boyolangu for approximately five months. Data collection techniques include participatory observation, in-depth interviews, and documentation of student artworks. The results show a significant increase in the aspect of learning independence, which is reflected in students' initiative in managing projects independently, as well as in the aspect of visual creativity, seen from the diversity of materials and techniques in the resulting collage artworks. Students were also able to display personal expression through emotionally meaningful themes. These findings support constructivism and humanistic theories, and reinforce the results of previous research regarding the effectiveness of PjBL in art instruction. The research conclusion indicates that the combination of PjBL and mixed media collage not only improves the quality of visual arts instruction, but also fosters independent and creative character in students. The practical implications of this research can serve as a reference in the development of contextual, expressive, and student-centered art learning strategies.